The Power of Exports - Easterly, William; Reshef, Ariell; Schwenkenberg, Julia (2012)
The authors systematically document remarkably high degrees of concentration in manufacturing exports for a sample of 151 countries over a range of 3,000 products. For every country manufacturing exports are dominated by a few "big hits" which account for most of the export value and where the "hit" includes both finding the right product and finding the right market. Higher export volumes are associated with higher degrees of concentration, after controlling for the number of destinations a country penetrates. This further highlights the importance of big hits. The distribution of exports closely follows a power law, especially in the upper tail. These findings do not support a "picking winners" policy for export development; the power law characterization implies that the chance of picking a winner diminishes exponentially with the degree of success. Moreover, given the size of the economy, developing countries are more exposed to demand shocks than rich ones, which further lowers the benefits from trying to pick winners.